THE EFFECT OF IFRS IMPLEMENTATION IN THE GRAY INDEX: LEVERAGE, LIQUIDITY, PROFITABILITY, AND COMPANY SIZE ON FINANCIAL STATEMENT DISCLOSURE - Anik Irawati; Rieka Ramdhaniyah; Nolita Yeni Siregar; Reva Meiliana (Prosiding International conference on Information Technology and Business (ICITB), 2019)
The objective of the study was to determine the effect of IFRS Implementation in the Gray Index: Leverage, Liquidity, Profitability, and Firm Size on Disclosure of Financial Statements. The independent variables in this study were the Gray Leverage Index, the Gray Liquidity Index, the Gray Profitability Index, and the Gray Size Company Index, and the dependent variable was the Financial Statement Disclosure. The sample of this study was banking companies listed on the IDX. This study used the purposive sampling and obtained the sample of 32 banking companies. The data collection was done by the method of collecting data obtained from the banking financial statements obtained from the website idx.com and processed using SPSS version 20. Based on the results of the analysis showed that the Gray Index Company size affected the Disclosure of Financial Statements, while the Gray Leverage Index, Gray Liquidity Index, The Gray Profitability Index did not affect the Disclosure of Financial Statements.Keywords: Gray Leverage Index, Gray Liquidity Index, Gray Profitability Index, Company Size Gray Index and Financial Statement Disclosure